Measuring energy security performance within China: Toward an inter-provincial prospective. (15th April 2017) - Zhang, Long; Yu, Jing; Sovacool, Benjamin K.; Ren, Jingzheng
Abstract: China has been the world's largest energy consumer and producer for many years, yet while myriad studies have investigated Chinese performance on energy metrics compared to other countries, few to none have looked internally at Chinese provinces. This paper firstly develops a five-dimensional evaluation system centered on the energy security dimensions of availability and diversity, affordability and equality, technology and efficiency, environmental sustainability, and governance and innovation. It then correlates these dimensions to 20 distinct energy security metrics that are used to assess the energy security performance of 30 Chinese provinces, divided into eight regions. Our results reveal both trends in energy policy and practice as well as provincial status of comparative energy security for the year 2013. We find, for instance, that there is no province which performs well in all five of the energy security dimensions, and that all provinces confronted threats related to energy availability and diversity. We also demonstrate that in comparative terms, the Middle Reaches of Yellow River and the Northwest were the most energy-secure, while the Middle Reaches of Yangtze River and the Northeast were least energy-secure. Highlights: We assessed energy security for 30 Chinese provinces across five dimensions. Fuzzy AHP, PROMETHEE and Sensitivity Analysis are used to investigate. Western provinces perform better performance than eastern provinces in 2013. Energy availability and diversity is the most severe threat facing China's energy security. Developing renewable energy will help improve China's Provincial energy security significantly.